Engagement of Toll-like receptor 2 enhances interleukin (IL)-17+ autoreactive T cell responses via p38 mitogen-activated protein kinase signalling in dendritic cells. (1st October 2014) - Wei, R; Dong, L; Xiao, Q; Sun, D; Li, X; Nian, H
Summary: Functional analysis of single Toll-like receptors (TLRs) in vivo is necessary to understand how they shape the ocular inflammation involved in uveitis. In this study we explored the role and mechanisms of TLR-2 agonists on the autoreactive T helper type 17 (Th17) response in experimental autoimmune uveitis (EAU). Treatment by peptidoglycan (PGN), a specific TLR-2 agonist, remarkably increased mRNA levels of Th17-lineage genes interleukin (IL)-17A, IL-21 and RAR-related orphan receptor (ROR)γt and promoted antigen-specific Th17 response in EAU mice. A mixture of PGN and interphotoreceptor retinoid-binding protein peptide (IRBP161–180 ) could effectively induce EAU in the absence of complete Freund's adjuvant (CFA). PGN treatment also enhanced the pathogenic activities of activated antigen-specific Th17 cells in vivo . PGN significantly increased the production of IL-1β, IL-6 and IL-23 of dendritic cells (DCs) and enhanced their ability to promote IL-17 + uveitogenic T cells. Enhanced immunostimulatory activities of PGN-DCs depend upon p38 activation. Inhibition of p38 mitogen-activated protein kinase (MAPK) activity dramatically decreased IL-17 gene expression and antigen-specific Th17 responses stimulated by PGN-DCs. Our findings suggest that PGN treatment dramatically promotes the IL-17 + uveitogenic T cell responses via enhancing the immunostimulatory activities of DCs. This effect may be mediated, at least in part, by activation of the p38 signalling pathway in DCs.